PENGARUH KOMPETENSI MANAJERIAL DAN KOMPETENSI SUPERVISI KEPALA MADRASAH TERHADAP MOTIVASI BERPRESTASI GURU - Darwina, Darwina (Manajemen Pendidikan, 2019)
This research aims to analyze and examine the influence of principal?s managerial competence and supervision to teachers? achievement motivation at Madrasah Tsanawiyah Negeri in Bulukumba Regency, South Sulawesi. This research is a field study with a quantitative approach through the ex post facto method. Respondents in this study as many as 83teachers were taken 50% randomly from 166 teachers at Madrasah Tsanawiyah Negeri in Bulukumba Regency. The data collection technique used is a questionnaire then analysis using inferential statistics through regression analysis. The results of this study show that partially, the principal?s managerial competencies and supervision competencies influence positively and significantly towards teachers? achievement motivation. Simultaneously, the principal?s managerial competence and supervision also have positive and significant impact on the teacher's achievement motivation. This indicates that the level of teachers? achievement motivation, there is influence of managerial competence and supervision competence applied by the headmaster at Madrasah Tsanawiyah Negeri in Bulukumba Regency.Keywords: Managerial Competence, Supervision Competence, Motivation for Achievement